Diversity of entomopathogenic fungi from soils of eucalyptus and soybean crops and natural forest areas - Domingues, Maurício Magalhães [UNESP]; Dos Santos, Paula Leite [UNESP]; Gêa, Bianca Cristina Costa [UNESP]; de Carvalho, Vanessa Rafaela [UNESP]; Zanuncio, José Cola; Serrão, José Eduardo; Zanetti, Ronald; Wilcken, Carlos Frederico [UNESP] (My University, 2022)
Soils present high fungal diversity, including entomopathogenic species. These fungi are used in pest control, providing easy production, multiplication, application, and dispersion in the field. The objective of the present study was to evaluate entomopathogenic fungal diversity in soils from eucalyptus and soybean crops and natural forest areas. These fungi were isolated using the “Bait Method” with Tenebrio molitor (Linnaeus, 1758) (Coleoptera: Tenebrionidae) larvae from 10 soil samples per area, collected at 10 cm deep in a zig-zag pattern. The isolated entomopathogenic fungi were cultivated in Petri dishes using PDA medium and their mycelia separated after seven days of incubation in a BOD-type chamber. Species of Aspergillus, Beauveria, Cordyceps, Fusarium, Metarhizium, Penicillium and Purpureocillium were identified. The “Bait Method” with T. molitor larvae is efficient to isolate entomopathogenic fungi with higher diversity from soils of the natural forest than the cultivated area.
Diversidade de fungos entomopatogênicos em solos de culturas de eucalipto e soja e área de mata nativa
Keywords: Beauveria; biological control; Cordyceps; Fusarium; Metarhizium